2021
DOI: 10.1016/j.jsxm.2021.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of BDSM: A Systematic Review

Abstract: Introduction BDSM is an abbreviation used to reference the concepts of bondage and discipline, dominance and submission, sadism and masochism, enacted by power exchanges between consensual partners. In recent years, attention has shifted from the idea of BDSM as a pathological and tabooed niche practice towards viewing BDSM as a healthy form of intimacy. Aim This systematic review brings together all existing literature on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Thus, to perpetuate BDSM as pathological, when it is indeed a healthy form of intimacy for many (Wuyts & Morrens, 2022 ; Wuyts et al, 2020 ), can have harmful consequences in the therapeutic context. In such cases, it is possible that an erroneous association of kink or sexual fetishism with compulsion is partly to blame.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, to perpetuate BDSM as pathological, when it is indeed a healthy form of intimacy for many (Wuyts & Morrens, 2022 ; Wuyts et al, 2020 ), can have harmful consequences in the therapeutic context. In such cases, it is possible that an erroneous association of kink or sexual fetishism with compulsion is partly to blame.…”
Section: Discussionmentioning
confidence: 99%
“…De Neef et al ( 2019 ) as well as Wuyts and Morrens ( 2022 ) have systematically reviewed studies that have uncovered biological processes behind BDSM. Both reviews identified and discussed evidence related to hormonal and neurological workings involved in BDSM practice, mainly during and post-BDSM play.…”
Section: Proximate Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship underscores the intricate connection between tickle fetishism and BDSM, contributing to the complexity of tickling experiences within the broader framework of sexual behavior. Despite valuable insights into the biology of BDSM, including brain activation and hormonal changes ( Wuyts and Morrens, 2021 ), existing literature lacks a comprehensive understanding on tickle fetishism. Tickling fetishism shows an overlap with other fetishes, including foot fetishism (podophilia), suggesting potential connections between these various sexual preferences ( Provine, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nondelinquent participants with pedophilia may display rather normal neurobiology (Krüger & Kneer, 2021;van Kessel et al, 2022). A recent meta-analysis of the biology of BDSM concluded that during BDSM interactions, brain systems regarding reward (for both dominants and submissives) and pain and stress (for submissives) were involved (Wuyts & Morrens, 2022). Yet, their etiological account remains unclear.…”
Section: Neurobiologymentioning
confidence: 99%